The mental health workforce gap in low- and middle-income countries: a needs-based approach - Tim A Bruckner; Richard M Scheffler; Gordon Shen; Jangho Yoon; Dan Chisholm; Jodi Morris; Brent D Fulton; Mario R Dal Poz; Shekhar Saxena (The World Health Organization, 2011)
OBJECTIVE: To estimate the shortage of mental health professionals in low- and middle-income countries (LMICs). METHODS: We used data from the World Health Organization's Assessment Instrument for Mental Health Systems (WHO-AIMS) from 58 LMICs, country-specific information on the burden of various mental disorders and a hypothetical core service delivery package to estimate how many psychiatrists, nurses and psychosocial care providers would be needed to provide mental health care to the total population of the countries studied. We focused on the following eight problems, to which WHO has attached priority: depression, schizophrenia, psychoses other than schizophrenia, suicide, epilepsy, dementia, disorders related to the use of alcohol and illicit drugs, and paediatric mental disorders. FINDINGS: All low-income countries and 59% of the middle-income countries in our sample were found to have far fewer professionals than they need to deliver a core set of mental health interventions. The 58 LMICs sampled would need to increase their total mental health workforce by 239 000 full-time equivalent professionals to address the current shortage. CONCLUSION: Country-specific policies are needed to overcome the large shortage of mental health-care staff and services throughout LMICs.